Jovens, políticas públicas e estratégias administrativas: o papel das ideias e dos discursos na constituição do campo e na trajetória das políticas de juventude no Brasil - Souza, Wanderson Felício de (2016)
This dissertation aims to analyze how the ideas and discourses on youth and the way in which young people are recognized as subjects having rights influenced the constitution of youth policies in Brazil. We investigate how the issue is institutionalized at the federal level, as well as how the choice for certain management strategies, which constitute the main forms of action and public administration in the subject, are made. Government and civil society organization documents and non-structured interviews were the main empirical material used to structure the analysis, in order to identify the “ideas of youth” in the field. As our starting point we consider the use of rhetoric (metaphors and narratives implicated in the formation and history of the public policies for youth), the existence of discursive coalitions and the use of interpretative frames by actors in examining the inflection points of initiatives for youth in Brazil. Afterwards we identify the main ideas of “youth” and analyze how they oriented the recognition of young people as a different social segment related to their “youthful condition” and rights as citizens. Based on these concepts, we examine the creation and definition of the main functions of the National Youth Secretariat, using the concept of mainstreaming, and taking into account the formulation and the history of the National Program for Youth Inclusion (PROJOVEM), we discuss intersectoral public policies. The main contribution of this research is not only to demonstrate how ideas and discourses influence the formation of policies, but also how social constructs that emerge from the field, sustained by recognizing young people as being citizens with rights, impact public management strategies. We conclude that despite the increasing importance attached to transversal management and intersectoral articulation in youth policy administration in Brazil, these concepts are the ones that guide the public management strategies and constitute the main limits for the daily operation of these policy choices by Brazilian public administration at the federal level.